2015
DOI: 10.1108/ijchm-09-2013-0421
|View full text |Cite
|
Sign up to set email alerts
|

The influence of self-esteem and role stress on job performance in hotel businesses

Abstract: Purpose – The main purpose of this study is to explore the influence of self-esteem and role stress on job performance in the hotel businesses. Moreover, the research aims to discover which role stress factors, i.e. role ambiguity, role conflict and role overload, have the most detrimental effect on an employee’s role stress in the hotel businesses. Design/methodology/approach – To achieve the above aim, four sets of hypotheses were prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
81
0
17

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(109 citation statements)
references
References 77 publications
11
81
0
17
Order By: Relevance
“…Within the hotel industry, situational constraint has been proven to exist such as inadequate training, excessive workloads and unsocial work hours (30) and role overload (31). Kao et al (32) maintained that hotel employees were faced with constraints from unsupportive superiors, colleagues and customers.…”
Section: Organizational Constraint and Workplace Deviant Behaviormentioning
confidence: 99%
“…Within the hotel industry, situational constraint has been proven to exist such as inadequate training, excessive workloads and unsocial work hours (30) and role overload (31). Kao et al (32) maintained that hotel employees were faced with constraints from unsupportive superiors, colleagues and customers.…”
Section: Organizational Constraint and Workplace Deviant Behaviormentioning
confidence: 99%
“…If the auditor is unable to complete the job well in accordance with the given time limit, then it indicates that the auditor's performance decreased. Research conducted by Akgunduz (2015) shows the different result that role overload is positively associated with job performance. Murtiasri and Ghozali (2006) found that role overload has no direct influence on job performance.…”
Section: Role Conflict and Performancementioning
confidence: 97%
“…The main purpose of the study conducted by Akgunduz (2015) is to explore the influence of self-esteem and role stress on job performance in the hotel businesses. Moreover, the research aims to discover which role stress factors, i.e.…”
Section: Role Conflict and Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Bireysel standartları, istekleri ve performans kapasitesini eşleştirmek, çalışanların özsaygısını olumlu yönde etkiler. Bu, çalışma standartları tutumlarına uyuyorsa, özsaygılarını geliştirme olasılıklarının daha yüksek olduğu anlamına gelir (Akgunduz, 2015(Akgunduz, : 1085. Bu doğrultuda oluşturulan hipotez;…”
Section: öZ Saygı Kavramı Ve Tüketici Davranışlarına Yansımalarıunclassified